Microcystic adnexal carcinoma of the head and neck: Characteristics, treatment, and survival statistics. Issue 1 (3rd December 2020) - Behbahani, Sara; Yeh, Christopher J.; Pinto, Jessica O.; Wassef, David; Povolotskiy, Roman; Joseph, Nia; Lambert, W. Clark; Schwartz, Robert A.
Abstract: Studies on microcystic adnexal carcinoma (MAC) survival rates have been limited. This effort examines the association of patient demographics, treatment modalities, and tumor stage with overall survival (OS) in patients with MAC of the head and neck. All cases of MAC with primary sites of the skin of the head and neck, confirmed histologically, and diagnosed from 2004 to 2016 in the National Cancer Database, were analyzed. We utilized Kaplan‐Meier and Cox proportional‐hazard models to analyze the characteristics and survival outcomes of the 415 cases that met the criteria. The mean age of diagnosis was 63.8 years (SD ±15.8). Mean OS was 10.8 years with 5‐ and 10‐year OS being 81.0% and 68.0%, respectively. Women were more frequently affected (59.0%; P  < .001). Stand‐alone primary site surgery was the most common treatment (81.4%): 15.9% of patients were treated with postexcision radiation therapy (RT). 18.3% were treated with RT with or without surgery and/or chemotherapy. RT was independently associated with a decreased hazard of death (HR = 0.23; P = .044). MAC of the head and neck disproportionately affects whites, is more common in women, and has the potential to metastasize. Surgical excision is the commonest treatment; our study shows benefit from judicious RT.